State of charge control based improved hybrid energy storage system for DC microgrid - Gajjar, Rital R.; Giri, Nimay Chandra; Patel, Unnati; Gajjar, Rakeshkumar C.; Dave, Dhavalkumar; Aly, Abouelmaaty M. (Institute of Advanced Engineering and Science, 2024)
This paper proposes a non-communication power management plan for a renewable solar-photovoltaic (PV) hybrid direct current (DC) microgrid consisting of batteries and supercapacitors (SCs). An effective control strategy for bidirectional converters has been proposed for power supply and load generation at different operating modes and state of charge (SOC) limits of the hybrid energy storage system (HESS). The battery and SC combination provides power to the load during normal or peak operating hours. The proposed hybrid power management system was tested under uneven load and generation using MATLAB. The proposed control enhanced the operation of microgrids by utilizing HESS with a novel control strategy based on the SOC. Seamless mode switches among different operating modes are also presented in this paper. This approach ensures stable current control, minimizes charging-discharging mode changes, mitigates the risk of overcharging and over-discharging batteries, extends battery service life, and balances the SOC across different energy storage units. Consequently, this strategy enhances the operational stability and economic efficiency of the DC microgrid. The proposed methodology provided better power allocation and improved the life of the battery.